BMSCs promote the differentiation of NSCs into oligodendrocytes via mediating Id2 and Olig expression through BMP/Smad signaling pathway. Issue 5 (21st September 2018) - Song, Peiwen; Xia, Xiang; Han, Tianyu; Fang, Huang; Wang, Ying; Dong, Fulong; Zhang, Renjie; Ge, Peng; Shen, Cailiang
Abstract : Neural stem cells (NSCs) have emerged as a promising treatment for spinal cord injuries. However, the increasing expression of bone morphogenetic proteins (BMPs) in spinal cord injury lesion sites seems to have contributed to the limited oligodendroglial differentiation and the majority of the astroglial differentiation of NSCs. In the present study, we demonstrate that BMPs promote NSCs differentiation toward astrocytes and prevent them from differentiating into oligodendrocytes. This effect is accompanied by the increasing expression of Id2 and the reduction in Oilg1/2 expression. Treatment with bone marrow stromal cells (BMSCs) can enhance the development of oligodendrocytes in the presence of BMPs. The analysis of Id2, as well as Olig1 and Olig2 gene expression, reveals that the effect of BMPs on these gene expressions is reversed with the addition of BMSCs. In sum, these data strongly suggest that BMSCs can promote the differentiation of NSCs into oligodendrocytes through mediating Id2 and Olig1/2 expression by blocking the BMP/Smad signaling pathway.